Transient and Recurrent Vision Loss in a High-Altitude Porter from Pakistan on a Polish Winter Karakoram Expedition - Robert K. Szymczak (MDPI AG, 2021)
Visual sensations appear in most migraine auras, but binocular blindness is uncommon. We described a case of multiple transient losses of vision in a man on a winter expedition to K2. His symptoms were later diagnosed as recurrent visual auras without pain. Sojourns at altitude can induce migraine attack; therefore, susceptible individuals should avoid factors that might provoke migraines at high altitude, such as improper acclimatization, dehydration and an inadequate sleep regime.